Adoption in the service of child protection: an international interdisciplinary perspective - Palacios, J; Adroher, S; Brodzinsky, D; Grotevant, H; Johnson, D; Juffer, F; Martínez-Mora, L; Muhamedrahimov, R; Selwyn, J; Simmonds, J; Tarren-Sweeney, M (American Psychological Association, 2019)
Existing over many centuries, adoption has been challenged in recent years by evidence about practices that do not respond to the principles, ethics and laws under which it should be enacted. Written from a multidisciplinary and international perspective, this article outlines the place of adoption in the child protection system, as well as its core elements of permanence and stability. Recent demographic changes in adoption throughout the world are first examined. The negative consequences of children's exposure to early adversities and the postadoption developmental trajectory of adopted people are also summarized. The focus of the argument is that adoption provides a legitimate model for the alternative care of children if undertaken within a rights and ethics framework that emphasizes children's best interests, as set out in international conventions and national laws. Implications for adoption policy and practice are presented.